Employee Perceptions on Human Resource Management Practices of the Local Government Unit of Kabayan, Benguet - Sumali-Gal-od, Marion Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of Human Resource Management (HRM) practices in the Local Government Unit of Kabayan, Benguet, and their relationship with sustainable local governance outcomes. Anchored on Strategic Human Resource Management, the study emphasized the alignment of HR practices with organizational goals, employee capability, accountability, and institutional performance. A quantitative descriptive-correlational research design was employed using a structured survey questionnaire adapted and contextualized from the PRIME-HRM framework and related HRM literature. The respondents were 130 regular, casual, and job order employees of the Local Government Unit of Kabayan, selected through total enumeration. Data were analyzed using weighted mean, variance, and Spearman’s rho correlation coefficient. Findings showed that HRM practices were generally implemented, particularly in recruitment and selection, learning and development, performance management, rewards and recognition, employee engagement and relations, and HR systems and institutional support. However, areas needing improvement included digital HR systems, communication processes, training needs assessment, feedback mechanisms, policy consistency, and strategic HR planning. Sustainable local governance outcomes were also generally evident, including quality public service, transparency and accountability, employee motivation and integrity, organizational adaptability, long-term institutional stability, service quality improvement, and community participation and satisfaction. The study concluded that HRM practices have a significant relationship with sustainable local governance outcomes, indicating that effective HRM contributes to organizational performance, employee commitment, institutional stability, and responsiveness to community needs. The study supports SDG 16, SDG 8, SDG 9, and SDG 11 by addressing strong institutions, decent work, innovation in HR systems, and sustainable local communities. Its sustainability impact lies in strengthening institutional capacity, workforce development, public service delivery, accountability, and governance continuity in a rural local government setting.
Keywords: Accountability; Employee Development; Human Resource Management; Institutional Stability; Local Government Unit of Kabayan; Public Service Delivery; Strategic Human Resource Management; Sustainable Local Governance; Transparency